SISTEM PENERIMAAN KAS PADA PT PRATAMA MITRA SEJATI JAKARTA - Maria Evy Purwitasari; Risma Cahyani; Rahmi Rosita (ASIAN PUBLISHER, 2024)
The purpose of this study was to determine the accounting system Cash Receipts disbursements in terms of the relevant parts, the documents used, and theinternal control system at PT Pratama Mitra Sejati..The research methodology was carried out in the form of a literature study by studying various forms of written materials, and field studies by means of observation and interviews.Based on the results of practical work, the authors conclude that cash disbursement accounting system at PT. Pratama Mitra Sejati is good.